Perfil epidemiológico da população de idosos do município de Marília-SP - Carvalho, Maria Helena Ribeiro de (2011)
This study aimed to describe the epidemiological profile of elderly residents in Marilia, a city in the interior of São Paulo, by means of an epidemiological and descriptive survey with a quantitative approach. We presented the mortality and morbidity of this population according to the causes and gender and divided into three age groups: 60-69 years, 70-79 years and 80 years and older in the period between 1998 and 2007. Data on the main causes of mortality and morbidity were compiled from the website of the Ministry of Health (www.datasus.gov.br) according to the International Classification of Disease, 10th Revision (ICD-10). The following indicators were applied: proportional mortality and mortality rates by age, gender, and causes of diseases; the mortality ratio for the calculation of morbidity; and hospitalizations rates. The five leading causes of mortality in the elderly were circulatory diseases, especially cerebrovascular disease and ischemic heart disease; neoplasias, with emphasis on prostate, breast, trachea, bronchi and lung cancer; respiratory tract diseases, including pneumonia and those related to lower respiratory tract; diseases of which causes were not fully or clearly defined; and in endocrine, nutritional and metabolic diseases, especially diabetes mellitus. The circulatory system diseases stand out as the leading cause of death among the elderly in all age groups studied, with mortality predominant among men. The causes of hospitalization of the elderly of both genders were due to circulatory, respiratory and digestive diseases, neoplasms, mental and behavioral disorders, injuries and poisoning, as well as certain other external causes. However they distinguished themselves by the position they occupied according to age group and gender. The prevalent cause of incidence in all age groups and both genders was linked to circulatory system diseases. The proportion of hospitalizations was predominant among men, and greater in women at age 80 years and older.